Reactive conformation of the active site in the hairpin ribozyme achieved by molecular dynamics simulations with ε/ζ force field reparametrizations - Mlýnský, Vojtěch; Kührová, Petra; Zgarbová, Marie; Jurečka, Petr; Walter, Nils G; Otyepka, Michal; Šponer, Jiří; Banáš, Pavel (The journal of physical chemistry. B, 2015)
X-ray crystallography can provide important insights into the structure of RNA enzymes (ribozymes). However, the details of a ribozyme's active site architecture are often altered by the inactivating chemical modifications necessary to inhibit self-cleavage. Molecular dynamics (MD) simulations are able to complement crystallographic data and model the conformation of the ribozyme's active site in its native form. However, the performance of MD simulations is driven by the quality of the force field used. Force fields are primarily parametrized and tested for a description of canonical structures and thus may be less accurate for noncanonical RNA elements, including ribozyme catalytic cores. Here, we show that our recent reparametrization of ε/ζ torsions significantly improves the description of the hairpin ribozyme's scissile phosphate conformational behavior. In addition, we find that an imbalance in the force field description of the nonbonded interactions of the ribose 2'-OH contributes to the conformational behavior observed for the scissile phosphate in the presence of a deprotonated G8(-). On the basis of the new force field, we obtain a reactive conformation for the hairpin ribozyme active site that is consistent with the most recent mechanistic and structural data.
Keywords: Crystallography, X-Ray; simulace molekulární dynamiky; Phosphates; ribosa; Protons; Ribose; fosfáty; protony; Molecular Dynamics Simulation; katalytická doména; RNA katalytická; Quantum Theory; DNA; RNA, Catalytic; Catalytic Domain; kvantová teorie; krystalografie rentgenová